2020
DOI: 10.1097/cm9.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature maintenance by forced-air warming blankets of different temperatures on changes in inflammatory factors in children undergoing congenital hip dislocation surgery

Abstract: Background Hypothermia is associated with many adverse clinical outcomes in pediatric patients, and thus, it is important to find an effective and safe method for preventing peri-operative hypothermia and its associated adverse outcomes in pediatric patients. This study aimed to investigate the effect of forced-air warming blankets with different temperatures on changes in the transforming growth factor-β (TGF-β), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-10 levels in children und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, in cancer treatment, several protocols were tested locally, such as hyperthermic intraperitoneal chemotherapy (Gelli et al, 2018; Lavoue et al, 2019), or using deep regional apparatus (Franckena et al, 2009; Overgaard et al, 1996; Pennacchioli, Fiore, & Gronchi, 2009). Recently, a clinical study showed that warming blankets (38°C) can be used to decrease inflammatory cytokines in patients after surgical treatment of hip displacement (He, Liu, Wen, & Wu, 2020; Petta et al, 2016). In inflammatory or infectious pathologies, hyperthermia was shown to have promising effects in sepsis‐induced acute lung injury in rats (Villar et al, 1994).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…However, in cancer treatment, several protocols were tested locally, such as hyperthermic intraperitoneal chemotherapy (Gelli et al, 2018; Lavoue et al, 2019), or using deep regional apparatus (Franckena et al, 2009; Overgaard et al, 1996; Pennacchioli, Fiore, & Gronchi, 2009). Recently, a clinical study showed that warming blankets (38°C) can be used to decrease inflammatory cytokines in patients after surgical treatment of hip displacement (He, Liu, Wen, & Wu, 2020; Petta et al, 2016). In inflammatory or infectious pathologies, hyperthermia was shown to have promising effects in sepsis‐induced acute lung injury in rats (Villar et al, 1994).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…This relationship is especially true for infants, who generate heat through brown adipose tissue metabolism instead of shivering in low-temperature environments. This metabolism is innervated by sympathetic nerves and inhibited during general anaesthesia, further increasing the risk of IPH ( 17 19 ). Therefore, it is imperative to undertake appropriate warming measures for children during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, active warming strategies are more effective, and the effects have been verified in adult patients ( 21 ). Active warming strategies generally include forced-air warming blankets ( 19 , 22 ), infusion heating apparatuses ( 23 ), forced air warmers ( 24 ), body cavity lavage liquid heating ( 25 ), increasing operating room temperature ( 26 ), etc. In addition, some studies have pointed out that prewarming 30–60 min before the operation can effectively decrease the incidence of IPH by reducing the redistribution of core body temperature ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the effect of general anaesthesia, the body is no longer able to counteract the reduction in temperature by shivering or vasoconstriction [2] ,and Intraoperative hypothermia occurs when thermal autoregulation is abolished under general anesthesia [3] . Hypothermia, generally de ned as a core body temperature <36℃, can occur at any stage in the perioperative period [4] .In general, hypothermia causes peripheral vasoconstriction, an increase in blood viscosity and a reduced blood ow, which can ultimately lead to increased thrombogenic potential [5] , increases intraoperative blood loss and risk of transfusion, delayes wound healing [6] , increases length of hospital stay and health-related costs, metabolic dysfunction, and even death [7] . Thus, intraoperative maintenance of normothermia is strongly recommended by several versions of the enhanced recovery after surgery (ERAS) guidelines as one of the major elements of perioperative care in colorectal surgery [8] .…”
Section: Introductionmentioning
confidence: 99%